Peran Budaya Literasi Pada Peningkatan Karakter Siswa Sekolah Dasar: Role Of Literation Culture On The Improvement Of Elementary School Student Characters - Puspita, Ari Metalin Ika (Universitas Muhammadiyah Sidoarjo, 2019)
The purpose of this study is to see the effect of the implementation of literacy culture on improving the character of elementary school students. The research method used in this study is quantitative research. The research design used in this study is quasi-experimental design with the design of one group Pretest-Posttest. The sampling technique used in this study was simple random sampling. Data analysis in this study used pair sample t-test with the help of SPSS 25.0. Based on the results of different tests using the Wilcoxon formula shows that the significance value is smaller than 0.05, it can be concluded that there is an influence of the Implementation of Literacy Culture on Improving Character of Elementary School Student.